Seasonal oceanography from physics to micronekton in the south-west Pacific. (March 2015) - Menkes, C.E.; Allain, V.; Rodier, M.; Gallois, F.; Lebourges-Dhaussy, A.; Hunt, B.P.V.; Smeti, H.; Pagano, M.; Josse, E.; Daroux, A.; Lehodey, P.; Senina, I.; et al.
Abstract: Tuna catches represent a major economic and food source in the Pacific Ocean, yet are highly variable. This variability in tuna catches remains poorly explained. The relationships between the distributions of tuna and their forage (micronekton) have been mostly derived from model estimates. Observations of micronekton and other mid-trophic level organisms, and their link to regional oceanography, however are scarce and constitute an important gap in our knowledge and understanding of the dynamics of pelagic ecosystems. To fill this gap, we conducted two multidisciplinary cruises (Nectalis1 and Nectalis2) in the New Caledonian Exclusive Economic Zone (EEZ) at the southeastern edge the Coral Sea, in 2011 to characterize the oceanography of the region during the cool (August) and the hot (December) seasons. The physical and biological environments were described by hydrology, nutrients and phytoplankton size structure and biomass. Zooplankton biomass was estimated from net sampling and acoustics and micronecton was estimated from net sampling, the SEAPODYM ecosystem model, a dedicated echosounder and non-dedicated acoustics. Results demonstrated that New Caledonia is located in an oligotrophic area characterized by low nutrient and low primary production which is dominated by a high percentage of picoplankton cyanobacteria Prochlorococcus (>90%). The area exhibits a large-scale north–south temperature and salinity gradient. The northern area is influenced by the equatorial Warm Pool and the South Pacific Convergence Zone and is characterized by higher temperature, lower salinity, lower primary production and micronekton biomass. The southern area is influenced by the Tasman Sea and is characterized by cooler temperature, higher salinity, higher primary production and micronekton biomass. The dynamic oceanography and the complex topography create a myriad of mesoscale features including eddies, inducing patchy structures in the ecosystem. During the cool season, a tight coupling existed between the ocean dynamics and primary production, while there was a stronger decoupling during the hot season. There was little difference in the composition of mid-trophic level organisms (zooplankton and micronekton) between the two seasons. This may be due to different turn-over times and delays in the transmission of primary production to upper trophic levels. Examination of various sampling gears for zooplankton and micronekton showed that net biomass estimates and acoustic-derived estimates compared reasonably well. Estimates of micronekton from net observations and the SEAPODYM model were in the same range. The non-dedicated acoustics adequately reproduced trends observed in zooplankton from nets, but the acoustics could not differentiate between zooplankton and micronekton and absolute biomasses could not be calculated. Understanding the impact of mesoscale features on higher trophic levels will require further investigation and patchiness induced by eddies raises the question of how to best sample highly dynamic areas via sea experiments.